2022
DOI: 10.1155/2022/3993452
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cell Salvage on Bleeding and Transfusion Needs in Cardiac Surgery

Abstract: Introduction. Cell salvaging is well established in the blood management of cardiac patients, but there remain some concerns about its effects on perioperative bleeding and transfusion variables. This randomized controlled study investigated the potential effects of the centrifuged end-product on bleeding, transfusion rates, and other transfusion-related variables in adult cardiac surgery patients submitted to extracorporeal circulation. Materials and Methods. Patients were randomly chosen to receive (cell-sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In twelve RCTs, involving 2129 participants in both the intervention group (n = 1061) and the control group (n = 1068), the effectiveness of using the Cell Salvage was compared with the control group, where traditional methods based on allogeneic transfusion were employed. Five studies showed a high risk of bias [ 26 , 41 , 43 , 46 ], while one study demonstrated an adequate level of quality [ 29 , 33 , 34 , 36 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In twelve RCTs, involving 2129 participants in both the intervention group (n = 1061) and the control group (n = 1068), the effectiveness of using the Cell Salvage was compared with the control group, where traditional methods based on allogeneic transfusion were employed. Five studies showed a high risk of bias [ 26 , 41 , 43 , 46 ], while one study demonstrated an adequate level of quality [ 29 , 33 , 34 , 36 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven RCTs with a total sample size of 2443 participants, considering the intervention group (n = 1203) and the control group (n = 1239), compared the efficacy of Cell Salvage use with the control group on the number of RBC units (n = 673) and platelets (n = 530). Four studies showed low risk of bias [ 26 , 32 , 34 , 50 ] and two studies showed medium risk of bias [ 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation